Leukotrienes, a potential target for Covid-19 (2020)
Repositioning of clinically approved drugs that may reduce the severity, hospitalization events, and time of recovery from SARS-CoV2 infection is a global health priority. Clinical reports of drug effects and lung pathology are providing insight into the pathogenesis of Covid-19, and comparison of these findings with our knowledge of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) can be used to develop rational hypotheses to prioritize clinical studies of available therapeutics. Recently, Cao and colleagues [1] investigated the addition of a lopinavir-ritonavir regimen to standard of care, which previously showed promising activity in an open-label clinical study of patients affected by SARS [2]. However, lopinavir-ritonavir therapy did not confer any clinical benefit for patients with Covid-19, even when patients received glucocorticoids as a supportive drug [1]. Several agents, including remdesivir and chloroquine/hydroxychloroquine alone or in combination with azithromycin, were tested as potential treatment for Covid-19 patients, however available data are still not sufficient to delineate a definitive therapeutic approach [